The packing and covering of the complete graph I: the forests of order five - Y. Roditty (International Journal of Mathematics and Mathematical Sciences)
The maximum number of pairwise edge disjoint forests of order five in the complete graph Kn, and the minimum number of forests of order five whose union is Kn, are determined.